Low voltage and variable-pressure scanning electron microscopy of fractured composites - de Oliveira Hein, Luis Rogerio [UNESP]; de Campos, Kamila Amato [UNESP]; Reis de Oliveira Caltabiano, Pietro Carelli [UNESP] (Pergamon-Elsevier B.V. Ltd, 2012)
Uncoated fracture surfaces of carbon-epoxy composites are investigated using a variable-pressure environmental scanning electron microscope (VP-ESEM), under optimized conditions for topographic description, image quality and sample preservation. Always using freeware or open source programs, parameters for low-voltage and low vacuum are stipulated with the support of Monte Carlo simulations combined to topographic measurements, tailoring the VP-ESEM setup for visualization of fine relief details. Based on topographic information from atomic force microscope (AFM) images, finest fracture steps were measured. These were the references to optimize and define boundaries for applied beam voltages and chamber pressures, restricted by the beam penetration depth and gas-electron interactions, guided by Monte Carlo simulations and signal-to-noise measurements. For VP mode, ideal chamber pressure was found around 30-40 Pa at 3 keV beam voltage and 6 mm working distance. Lower pressures will cause noise due to electron charging and gas excess provokes resolution degradation and noise due to positive charging and electron beam scattering, raising the skirt radius. When a larger working distance is necessary, it can be compensated by adjusting the detector bias and the probe current, or even lowering chamber pressure, but the signal-to-noise ratio will certainly change. Monte Carlo simulations provided a good approach to optimize imaging conditions under low vacuum and low voltage for fractographic analysis of carbon-epoxy composites. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Monte Carlo; Low voltage; Variable pressure scanning electron microscope; Signal-to-noise ratio